2017
DOI: 10.1093/jhps/hnw051
|View full text |Cite
|
Sign up to set email alerts
|

Hip arthroscopy results in improved patient reported outcomes compared to non-operative management of waitlisted patients

Abstract: Hip arthroscopy (HA) is an established treatment option to address intra-articular pathology of the hip. However, some clinicians encourage non-operative management (NOM). Non-operative management may include active measures such as physiotherapy and intra-articular steroid injections, or NOM may involve so called watchful waiting with no active intervention. These approaches, along with surgery have been detailed recently in the Warwick Agreement, a Consensus Statement regarding diagnosis and treatment of Fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…In a study of patients in a national health care system, patients who were waitlisted for surgery had notably lower PRO scores than patients who were able to schedule surgery quickly. 12 In a system with private payers, Dierckman et al 24 likewise determined that increased symptom times were correlated with lower PRO scores on a logarithmic scale. Aprato et al found that patients who had delayed arthroscopy with preoperative symptoms lasting greater than three years had notably worse outcomes than those with shorter symptom durations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of patients in a national health care system, patients who were waitlisted for surgery had notably lower PRO scores than patients who were able to schedule surgery quickly. 12 In a system with private payers, Dierckman et al 24 likewise determined that increased symptom times were correlated with lower PRO scores on a logarithmic scale. Aprato et al found that patients who had delayed arthroscopy with preoperative symptoms lasting greater than three years had notably worse outcomes than those with shorter symptom durations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a comparison of arthroscopic treatment with nonoperative management for FAI has demonstrated clinically meaningful improvements in patient-reported hip function and quality of life in the arthroscopic population. 12 …”
mentioning
confidence: 99%
“… 29 A recent study showed significantly improved patient-reported outcomes in patients aged < 60 years who underwent hip arthroscopy for FAI when compared with a cohort that was waitlisted. 30 Both groups had undergone three months of conservative treatment including community physiotherapy before either having the arthroscopy or being waitlisted. In another study evaluating high-level athletes, return to their high-level sport after hip arthroscopy was measured as 3/4 by one year post-operatively.…”
Section: Hip Arthroscopymentioning
confidence: 99%
“…The length of the waiting period for consultation and/or surgery can potentially have an impact on the patient's quality of life or an athletes' performance, as well as financial impacts in terms of cost related to time loss from work, physiotherapy treatments, and pain management . While this has been extensively investigated for hip and knee arthroplasty, there is no published data that analyse the wait time and the referral processes for patients needing hip arthroscopy.…”
Section: Introductionmentioning
confidence: 99%